Occupational Health and Safety (OHS) Analysis Using HIRARC and 5S Methods (Case Study: PT. XYZ) - I Gusti Ayu Sri Deviyanti; Bintang Anugrah Illahi; Putu Anggi Suryantari (Universitas Katolik Darma Cendika, 2026)
PT. XYZ is a manufacturing company engaged in plastic-based injection moulding services according to customer demand. Its production activities involve potential hazards and workplace accident risks. The problem identified in this study is that the implementation of Occupational Health and Safety (OHS) in the production area is not yet optimal, indicated by workers’ lack of discipline in using personal protective equipment (PPE), poorly organized work areas, and machine operations with accident potential. This study aims to analyze potential hazards and occupational risk levels using the HIRARC and 5S methods. The research applied a qualitative case study approach through observation, interviews, and documentation. The results identified 16 potential hazards, consisting of 1 high-risk category (7%), 9 moderate-risk categories (60%), and 6 low-risk categories (33%). The highest risk was workers’ hands being trapped in the injection moulding machine. Based on the 5S analysis, several work areas still did not meet OHS standards, including poor material arrangement, scattered plastic waste, inadequate machine maintenance, and low compliance with PPE use. Therefore, the company needs to improve risk control through SOP improvements, stricter PPE supervision, routine machine maintenance, and implementation of the 5S work culture.